"Opportunity to Learn" Effect on Mathematics Achievement in Basic Education in Argentina - Rubén Alberto Cervini Iturre (Universidad Autónoma de Baja California, 2001)
This study investigated the relationship between the 'opportunity to learn' (OTL) offered by the teacher to students in the classroom and their mathematics achievement. The data are 32,156 7th and 6th graders (primary education) enrolled in 1,497 classroom of urban schools in Argentina. Multilevel linear modeling with two levels (student and classroom) was used to analyze OTL effects on achievement. Student math score was based on an standard test applied to the students at the end of the academic year. Three different indicators from a teacher questionnaire were used to measure OTL concept. It was found that all of them are significant predictors of mathematics test score even after students socioeconomic background, socioeconomic school context and level of educational resources in school were controlled. The data behavior shows that (1) OTL is an important intermediate variable between socioeconomic school context and achievement and (2) it is a multidimensional concept. In consequence different indicators should be used in order to properly estimate the effect of OTL on achievement.